All Days 2015
DOI: 10.2118/176291-ms
|View full text |Cite
|
Sign up to set email alerts
|

Redesign of a Single String Packerless ESP-Gas Lift Hybrid

Abstract: The Kaji-Semoga fields in South Sumatra, Indonesia, are mature, waterflooded oil fields with ESP's in more than half the wells. To minimize oil deferment due to down-hole ESP problems, an ESP-gas lift hybrid was implemented in 2009. The idea was to install gas lift as a backup so the well could be kept on production, albeit at reduced rate, until the ESP could be serviced or replaced. During the period 2011-2012, 97 wells had the hybrid lift system installed and ESP problems occurred 23 times in these wells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In Indonesia, the heavy oil production in wells with depths greater than 3000 feet using ESP alone posed many challenges, so a combination of ESP and GL using only one valve was tested (Prakoso et al 2010), and the results showed that it prevented the loss of 4,400 barrels of oil in one year. Furthermore, Rohman et al (Rohman et al 2015) continued to develop the system using more than one valve, and the production rate of wells increased from 36% to more than 50% compared to the case when ESP was used only with the original GL design. However, the application of this combined method has not been widely disseminated in the world, so further research is still needed on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the heavy oil production in wells with depths greater than 3000 feet using ESP alone posed many challenges, so a combination of ESP and GL using only one valve was tested (Prakoso et al 2010), and the results showed that it prevented the loss of 4,400 barrels of oil in one year. Furthermore, Rohman et al (Rohman et al 2015) continued to develop the system using more than one valve, and the production rate of wells increased from 36% to more than 50% compared to the case when ESP was used only with the original GL design. However, the application of this combined method has not been widely disseminated in the world, so further research is still needed on this issue.…”
Section: Introductionmentioning
confidence: 99%